Fieldwork Implementation in Sendang Biru Karst Area of Malang Regency: A Technical and Operational Review - Ainul Labib, Mohammad; Nasution; Surjanti, Jun (Technium Social Sciences Journal, 2025)
Teaching and learning activities cannot only be done in a closed space classroom, but also can be done in an opened space or outside the classroom by doing a fieldwork study. Fieldwork study can practically give an understanding of the field condition of the environment. The aim of this study is to figure out the technical and operational aspects of fieldwork implementation in Sendang Biru karst area. This study is a kind of descriptive qualitative research with literature study approach. The subjects of this study are the students who do a fieldwork study in the study area. The objects of this study area the environment situation and condition, as well as the social and culture in the fieldwork area and around Sendang Biru Karst area. The operational aspects review by identifying the needs and the supply of natural resources. The results of the study show the karst landscape condition has unique characteristics hat can be used as a fieldwork study area. The technical aspects show a study of feasibility of the study area that can be used as spots that can be learned. The operational aspects have the things that allow a fieldwork study in Sendang Biru Karst area.